Mine haul road rolling resistance: influences and impacts - Coffey, Jarrad Patrick (Curtin University, 2015)
Energy efficiency of haulage, in the production of mineral ores, was investigated through measurement of the rolling resistance experienced by haul trucks while traversing unsealed, unbound granular pavements. It appears pavement surface condition influences rolling resistance more significantly than pavement structural capacity. Validation of various modelling methods with in-situ pavement deflection measurements showed that simple methods are able to estimate pavement surface deflection with similar accuracy to more complex techniques, such as Finite Element Analysis.